Depreciating Indian Rupee: Trends and Issues - BADAR ALAM IQBAL (Global Economic Observer, 2015)
Indian rupee has been depreciating since May 2013 creating many dimensional trends and issues to be looked at or to be examined. If a currency is depreciating it implies that the value has gone down in relation to another currency. Presently, the value of rupee has declined from nearly Rs. 55 to a dollar to nearly 69 rupees a dollar. This is because portfolio investors are now taking back their money from emerging markets causing demand for dollars (international currency for payments) to increase hence, pulling down Indian currency. The present paper analyzing the deprecating trends since independence in the context of Indian economy and also discusses issues which have come up due to depreciation of Indian rupee.